AN ASSESSMENT OF HEAVY METAL CONCENTRATIONS IN THE SCLERACTINIAN CORAL TISSUES OF KARIMUNJAWA ARCHIPELAGO, INDONESIA - Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Karimunjawa archipelago, marine national park, has been considered to be a relatively pristine area that have more than 90 species of corals. This study was conducted to detect any concentrations heavy metal levels in the tissues of eight coral species. Based on life-forms, selected coral species are classified as massive (Porites lutea and Goniastrea retiformis), submassive (Galaxea fascicularis and Stylophora pistillata), foliaceous (Pavona decussata and Montipora foliosa) and branching/ramosa (Acropora aspera and Pocillopora damicornis). The concentration of heavy metals in the coral tissues were assessed using Atomic Absorption Spectrophotometer (AAS) technique. The present experimental results demonstrated that metal in coral tissues were no significant difference between sites. Concentration levels of five heavy metals were found to be in the order of Pb>Zn>Cr>Cd>Cu. Relating heavy metal concentrations to life-form corals, there were no significant differences of all the metals (except Pb), the highest concentration of Pb were found in foliaceous type of corals. The high level of Pb in foliaceous coral life-form (Pavona decussata and Montipora foliosa), indicating that these coral species are usefull as potential candidates of biomonitoring material for this metal. However, the use of corals as biomonitors should be considered carefully in biological and local environmental factors.